Targeting PCSK9, through an innovative cVLP-based vaccine, enhanced the therapeutic activity of a cVLP-HER2 vaccine in a preclinical model of HER2-positive mammary carcinoma - Laura Scalambra; Francesca Ruzzi; Olga Maria Pittino; Maria Sofia Semprini; Chiara Cappello; Stefania Angelicola; Arianna Palladini; Patrizia Nanni; Louise Goksøyr; Cyrielle Fougeroux; Manuel L. Penichet; Adam Frederik Sander; et al. (Journal of Translational Medicine)
Abstract Background HER2-targeted therapies have revolutionized the treatment of HER2-positive breast cancer patients, leading to significant improvements in tumor response rates and survival. However, resistance and incomplete response remain considerable challenges. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibition is a novel therapeutic strategy for the management of dyslipidemia by enhancing the clearance of low-density lipoprotein cholesterol receptors, however recent evidence also shows links between PCSK9 and cancer cells. We present an innovative immunization approach combining capsid virus-like particle (cVLP)-based vaccines against HER2 and PCSK9. Methods The therapeutic activity of the combined vaccine was evaluated in female mice challenged with HER2-positive mammary carcinoma cells. Controls included untreated mice and mice treated with cVLP-PCSK9 and cVLP-HER2 as standalone therapies. Antibodies elicited by vaccinations were detected through ELISA immunoassay. The functional activity of the antibodies was tested in 3D-soft agar assay on human HER2 +  +  + trastuzumab sensitive and resistant cells. Results Mice vaccinated with cVLP-HER2 + cVLP-PCSK9 displayed tumor regression from the 40th day after cell challenge in 100% of mice remaining tumor-free even 4 months later. In contrast, 83% of mice treated with cVLP-HER2 vaccine alone experienced an initial tumor regression, followed by tumor relapse in 60% of subjects. Untreated mice and mice treated with the cVLP-PCSK9 vaccine alone developed progressive tumors within 1–2 months after cell injection. The combined vaccine approach elicited strong anti-human HER2 antibody responses (reaching 1–2 mg/ml range) comprising multiple immunoglobulins isotypes. cVLP-PCSK9 vaccine elicited anti-PCSK9 antibody responses, resulting in a marked reduction in PCSK9 serum levels. Although the anti-PCSK9 response was reduced when co-administered with cVLP-HER2, it remained significant. Moreover, both cVLP-HER2 + cVLP-PCSK9 and cVLP-HER2 alone induced anti-HER2 antibodies able to inhibit the 3D growth of human HER2 +  +  + BT-474 and trastuzumab-resistant BT-474 C5 cells. Strikingly, antibodies elicited by the combined vaccination were more effective than those elicited by the cVLP-HER2 vaccine alone in the inhibition of trastuzumab-resistant C5 cells. Conclusions The results indicate that cVLP-PCSK9 vaccination shows adjuvant activity when combined with cVLP-HER2 vaccine, enhancing its therapeutic efficacy against HER2-positive breast cancer and holding promise in overcoming the challenges posed by resistance and incomplete responses to HER2-targeted therapy.